O discurso sobre a educação básica do campo: uma análise linguístico-discursiva do tom de obrigatoriedade do enunciador - Assunção, Rosalina Brites de (2011)
This paper intends to investigate how an obligatory tone is constructed in the texts that materialize the Landless Workers Movement (MST) and the Ministry of Education and Culture (MEC) discourse about an educational proposal to the rural population. Our corpus is based on five texts that belong to the Dossiê MST School collection and two of the National Council of Education/MEC Resolutions: Resolution CEB/CNE nº 1/2002 and Resolution CEB/CNE nº2/2008. At first, the aim is to analyze the discourse strategies that both enunciators used in their discourses, to produce a demanding tone in the enunciation, permitting to outline the image which they construct of themselves in the discourse. Secondly, it seeks to discover, through the analysis of the heterogeneity enunciative of each discourse, the ideological position of the enunciators and to reveal their intention within their education proposal. The analysis was made according to the theoretical assumptions of the French line of the Discourse Analysis as presented in Maingueneau (2004, 2008), Orlandi (2007), Brandão (2004), Amossy (2005). The issues that focus on enunciation projection in the statements are linked to the ideas of the Enunciation theory, based on the studies of Benveniste (1989), Authier-Revuz (2004), Fiorin (1999). The linguistic modalization analysis is subsidized by the Functionalist theory according to Halliday (1985), Hengeveld (2004), Palmer (1986) and Neves (2007). The results demonstrate that the idea of obligation shown in both discourses is constructed in a different way. The enunciative organization shows that, in the MST discourse, the tone of obligation is more impositive, which at discourse surface, behaves as an emancipation role. In the governments discourse, MEC, the tone is less mandatory and has the paper to include the countrymen in the culture and values of the burgeoise society. However, the hypothesis which is intended to be proved is that the option for the mandatory tone used by both enunciators is a discourse strategy which is constituted as by a power dispute between equality and difference, in which the MEC discourse intends to silence the MST movement and the MST aims to unstable the State s Education proposal.